2016
DOI: 10.5603/cj.a2015.0080
|View full text |Cite
|
Sign up to set email alerts
|

The impact of admission red cell distribution width on long-term cardiovascular events after primary percutaneous intervention: A four-year prospective study

Abstract: Background: Red cell distribution width (RDW) is an indicator of erythrocyte in different size, and its prognostic value has been demonstrated in numerous cardiac (Cardiol J 2016; 23, 3: 281-288)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…Ghaffari et al reported that an elevated baseline RDW could predict adverse outcomes in patients with STEMI undergoing thrombolytic therapy, during a follow-up period of (7.7 ± 3.2) months [ 19 ]. Isik et al studied the effects of RDW level on long-term prognosis in 96 STEMI patients who underwent primary PCI, and finally found that admission RDW level was an independent predictor of long term Mace [ 20 ]. To our knowledge, the main finding of our study is the first report showing the combined value of RDW and the GRACE score in predicting Mace at 36-month follow-up in patients with STEMI who underwent primary PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghaffari et al reported that an elevated baseline RDW could predict adverse outcomes in patients with STEMI undergoing thrombolytic therapy, during a follow-up period of (7.7 ± 3.2) months [ 19 ]. Isik et al studied the effects of RDW level on long-term prognosis in 96 STEMI patients who underwent primary PCI, and finally found that admission RDW level was an independent predictor of long term Mace [ 20 ]. To our knowledge, the main finding of our study is the first report showing the combined value of RDW and the GRACE score in predicting Mace at 36-month follow-up in patients with STEMI who underwent primary PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of RDW for short-term or long-term cardiovascular events have been demonstrated in STEMI patients [ 20 , 25 ]. In a meta-analysis involving 80216 patients from 22 studies, RDW was a remarkably strong predictor of all-cause mortality (HR = 1.80, 95% CI:1.35–2.41, P < 0.001) and non-fatal adverse events (HR = 1.86, 95% CI:1.50–2.31, P < 0.001), although there was significant heterogeneity in the different studies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another large population study, including as many as 1,760 coronary angiography patients, Gijsberts et al (22) reported that each one standard deviation (SD) increase of RDW was associated with a 19% higher risk of MACE in multivariable, fully adjusted analysis (HR, 1.19; 95% CI; 1.08-1.32; P<0.001). The relationship between RDW and 4-year cardiovascular events after PCI was also investigated in 96 consecutive patients with ACS by Isik et al (23), who finally reported that an increased RDW value was an independent predictor of long-term MACE (HR 5.26; 95% CI, 1.71-16.10; P=0.004). More recently, Ghaffari et al studied 312 patients undergoing thrombolysis for ACS (24), and reported that RDW was an independent predictor of in-hospital occurrence of MACE (RR, 3.17; 95% CI, 1.23-8.46; P=0.017).…”
Section: Discussionmentioning
confidence: 99%
“…-Eight studies identified as Cohort (including two identified as a retrospective cohort and five identified as a prospective cohort) [20][21][22][23][24][25][26][27].…”
Section: : Total Number Of Articles After Applying Inclusion/exclusimentioning
confidence: 99%